Spatial distribution of pits on stainless steel - Salvarezza, Roberto Carlos (1990)
The spatial distribution of pits formed on a stainless steel electrode is analysed by means of two stochastic criteria based on the Poisson distribution law. Information is obtained about the character of the location of pits on the electrode surface.